1992
DOI: 10.1002/ar.1092320102
|View full text |Cite
|
Sign up to set email alerts
|

Correlated biochemical and radioautographic studies of protein turnover in developing rat incisor enamel following pulse‐chase labeling with L‐[35S]‐ and L‐[methyl‐3H]‐methionine

Abstract: The movement of proteins into and out of enamel was followed over time using a highly sensitive microprecipitation technique to quantify the amount of TCA-insoluble radioactivity present within small pieces of freeze-dried enamel and cells (enamel organ) dissected from the mandibular incisors of rats injected with L-[35S]-methionine. Conventional image processing techniques were also used to estimate the number of silver grains over enamel and cells in radioautographs of mandibular incisors from rats similarly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Samples were collected from this mixture at 0, 2, 4, 8, 24, 48, 72, and 168 hr and immediately stored at −20 °C. Radiolabel stability in the conjugate was quantified by precipitating large ELP fragments (> 10 kDa) with 100 μL 16.5% cold trichloroacetic acid [38]. Low MW degradation products (< 10 kDa) in the supernatant and larger ELP species in the pellet were measured on a γ-counter and the loss of label was obtained by dividing the supernatant radioactivity by the total radioactivity in the supernatant and pellet at each time point.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were collected from this mixture at 0, 2, 4, 8, 24, 48, 72, and 168 hr and immediately stored at −20 °C. Radiolabel stability in the conjugate was quantified by precipitating large ELP fragments (> 10 kDa) with 100 μL 16.5% cold trichloroacetic acid [38]. Low MW degradation products (< 10 kDa) in the supernatant and larger ELP species in the pellet were measured on a γ-counter and the loss of label was obtained by dividing the supernatant radioactivity by the total radioactivity in the supernatant and pellet at each time point.…”
Section: Methodsmentioning
confidence: 99%
“…(3) during the first half of the maturation stage, modulating ameloblasts secrete proteins some of which appear to be amelogenins (Nanci et al, 1987a(Nanci et al, ,b, 1989aMcKee et al, 1988;Inage et al, 1989Inage et al, , 1996Smith andNanci, 1989, 1996;DenBesten and Li, 1992;Smith et al, 1992;Fong et al, 1996a;Wurtz et al, 1996), and therefore protein secretion is not an activity excluded from "resorptive" ameloblasts;…”
Section: Endocytosis and Pinocytosismentioning
confidence: 96%
“…Studies on the components of the enamel matrix have encountered a series of difficulties chiefly arising from the heterogeneous composition of the matrix, which is partly due to the secretion of a variety of proteins by the ameloblasts, and partly to the post-secretory sequential degradation of these proteins Smith et al 1992). Probably because it is secreted by ameloblasts, that is, by ectodermal cells, and also because of its high sulfur content, it has been suggested that the organic matrix of immature enamel could consist of keratin-related proteins (Eastoe 1963).…”
Section: Matrix Componentsmentioning
confidence: 99%